Gender Portrayal in Edufa and in the Chest of A Woman - Nugah, E.B. (University of Ghana, 2013)
This work examines gender portrayal in Edufa by Efua Theodora Sutherland and In the Chest of a Woman by Efo Kodjo Mawugbe both of whom are of blessed memory. It considers Sutherland as the mother of modern Ghanaian Drama and Mawugbe as an icon of Ghanaian Drama; assessing their contributions and achievements as playwrights and dramatists in Ghana. An in-depth analysis of the plays was carried out to ascertain the conflicts and messages imbedded in them. The study was based mainly on library materials including journals, articles, play texts, book of tributes and other relevant information on the playwrights. The investigation arrived at the conclusion that both Sutherland and Mawugbe witnessed male domination and female marginalisation in Ghana from the 1960’s. Both dramatists represented excellently the issue of gender imbalance in Ghana in their plays. They also encouraged female empowerment and the need for change in certain practices in society which tend to hinder progress. The on-going struggle against gender imbalance in society, especially in Ghana is undoubtedly reflected in the plays. The study also underscores some misconceptions and dangers that surround what gender represents.
Thesis (MPhil) - university of Ghana,2013
Keywords: The Chest of a Woman; Portrayal; Drama